A Comparison of the Currently Used Nodal Stage Classification with the Number of Metastatic Lymph Nodes and the Number of Metastatic Lymph Node Stations for Non-Small Cell Lung Cancer; Which of These Is the Best Prognostic Factor? - Citak, Necati; Aksoy, Yunus; Isgörücü, Özgür; Obuz, Cigdem; Acikmese, Baris; Buyukkale, Songul; Metin, Muzaffer; Sayar, Adnan (Zentralblatt für Chirurgie - Zeitschrift für Allgemeine, Viszeral-, Thorax- und Gefäßchirurgie, 2019)
Objectives We aimed to compare the currently used nodal staging system (pN) with the number of metastatic lymph node (LN) stations (sN) and the number of metastatic LNs (nN) on survival in patients with NSCLC.Methods Between 2010 and 2017, 1038 patients resected for NSCLC were analyzed. We performed three-different stratifications of LN status assessment: pN-category (pN0, pN1 and pN2); sN-category (sN0, sN1; one station metastasis, sN2; two-three stations metastases, and sN3; ≥ 4 stations metastasis); nN-category (nN0, nN1; one-three LNs metastasis, nN2; four-six Lns metastasis, and nN3; ≥ 7 LNs metastasis).Results Five-year survival rate was 70.1% for N0 in all classifications. It was 54.3% for pN1, and 26.4% for pN2 (p < 0.0001). Five-year survival rates for N1, N2, and N3 categories were 54.1%, 42.4% and 16.1% according to sN, and 51.4%, 36.1%, and 7.9% according to nN, respectively (p < 0.0001). In multivariate analysis, sN and nN were independent risk factors such as pN (p < 0.0001). Hazard ratios versus N0 for N1, N2, and N3 were more significant for sN and nN than pN (1.597, 2.176, and, 3.883 for sN, 1.645, 2.658, and, 4.118 for nN, and 1.576, 3.222 for pN, respectively). When the subcategories of sN and nN were divided into pN1 and pN2 subgroups, the anatomic location of the LN involvement lost importance as tumor burden and tumor spreading increased.Conclusion The number of metastatic LN stations and the number of metastatic LNs are better prognostic factors than currently used nodal classification in NSCLC.
Keywords: non-small cell lung cancer; number of metastatic lymph node stations; number of metastatic lymph nodes; prognosis; staging